BIODIESEL PRODUCTION USING CANOLA OIL WITH HETEROGENEOUS CATALYST FROM CONVENTIONAL CALCIUM OXIDE VIA MICROWAVE ASSISTED METHOD - ZI YAN MICHELLE, LEOW (IRC, 2017)
The urge of resource demands and environmental issues are driving the global development of renewable energy. Biodiesel (alkyl esters) from vegetable oils or animal fats via transesterification is said to be the next promising bioenergy that can substitute petroleum- derived diesel fuel. Transesterification is a catalyzed process, hence homogeneous catalysts are employed for biodiesel production. Unfortunately, over the past few years, many problems related to this homogeneous catalyst have been reported. The purification process of free fatty acids tends to prolong the production and thus results in further complications hence, stimulating the conception of heterogeneous catalyzed transesterification. Despite the success of various heterogeneous catalysts, many are not viable for industrial usage as most of the catalysts are expensive and additional preparation method is needed. Some of the heterogeneous catalysts widely used by the industries are ZnO, KNO3 and CaO. Among these three heterogeneous catalysts, calcium oxide (CaO) shows great capability in catalyzing the reaction. Besides that, canola oil can be found abundantly in Malaysia. In addition, microwave assisted technique can save a lot of time and energy. Therefore, in this study, the effect of reaction time, alcohol-to-oil ratio, amount of catalyst and microwave frequency were investigated under microwave conditions. Based on the optimized condition, the biodiesel yield is 77 weight %. The optimization is done by using Response Surface Methodology (RSM) in which central composite design was used to determine the significance level and interactions effect of these parameters. In conclusion, this research shows that canola oil has a great potential to be a feedstock to produce biodiesel